Perancangan Sistem Informasi Pendaftaran Rawat Inap pada Layanan Kesehatan Rumah Sakit Umum Daerah Siti Fatimah - Alfin Cahyo Wibisono; Tata Sutabri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The purpose of setting up SIMRS is to improve efficiency, effectiveness, professionalism, performance, and access and services in hospitals. In the preparation of this paper, data was collected through observation methods, interviews, literature studies, and the application of software development models using the waterfall method. The result is the design of a web-based patient registration information system using Laravel and MySQL as a database. Hospitals face several problems, including data redundancy in the input process and less than optimal data presentation, making it difficult to manipulate, change, and delete data. The author hopes that the development of a new information system can simplify and speed up the data input process. The information system designed is expected to make it easier for patients to register online as well as assist admins in the patient registration process, making it easier to make registration reports.